2008
DOI: 10.1007/s00894-008-0318-8
|View full text |Cite
|
Sign up to set email alerts
|

The theoretical 3D structure of Bacillus thuringiensis Cry5Ba

Abstract: Cry5Ba is a delta-endotoxin produced by Bacillus thuringiensis PS86A1 NRRL B-18900. It is active against nematodes and has great potential for nematode control. Here, we predict the first theoretical model of the three-dimensional (3D) structure of a Cry5Ba toxin by homology modeling on the structure of the Cry1Aa toxin, which is specific to Lepidopteran insects. Cry5Ba resembles the previously reported Cry1Aa toxin structure in that they share a common 3D structure with three domains, but there are some disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Crystal structure of Cry III A has been published first [62] and several others are now available. Xia et al [63] predicted the first theoretical model of the three dimensional (3D) structure of a Cry (Cry 5Ba) toxin by homology modeling on the structure of the Cry1Aa toxin, which is specific to Lepidopteran insects. The three-domain structure of CryIIIA consisted of the following: an α-helical barrel (domain I) which shows some resemblance to membrane-active or sporeforming domains of other toxins [64]; a triangular prism of "Greek key" beta sheets (domain II); and a β-sheet jelly-roll fold (domain III) [62].…”
Section: General Structure Of Cry Toxinmentioning
confidence: 99%
“…Crystal structure of Cry III A has been published first [62] and several others are now available. Xia et al [63] predicted the first theoretical model of the three dimensional (3D) structure of a Cry (Cry 5Ba) toxin by homology modeling on the structure of the Cry1Aa toxin, which is specific to Lepidopteran insects. The three-domain structure of CryIIIA consisted of the following: an α-helical barrel (domain I) which shows some resemblance to membrane-active or sporeforming domains of other toxins [64]; a triangular prism of "Greek key" beta sheets (domain II); and a β-sheet jelly-roll fold (domain III) [62].…”
Section: General Structure Of Cry Toxinmentioning
confidence: 99%
“…So far, Cry1 toxins have extensively been used in studies of insect control either as transgenic spores or as spray formulations. Where three-dimensional crystal structure of Cry1 family of protein is concerned, few of the toxins in solutions have been analysed by X-ray diffraction crystallography [39], and a few of them have been predicted using the homology modelling method [1012]. All these toxins have a different toxicity spectrum; in spite of this, these proteins show a similar tertiary organization.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, solution of the threedimensional structure of all Cry1 family members is important for further investigations. So far, crystal structures of the active toxins in solutions have been analyzed for Cry3A (Li et al, 1991), Cry1Aa (Grochulski et al, 1995), Cry1Ac (Derbyshire et al, 2001), Cry3B (Galitsky et al, 2001), Cry2A protoxin (Morse et al, 2001), Cry4Ba (Boonserm et al, 2005), Cry4Aa (Boonserm et al, 2006) by X-ray diffraction crystallography, and subsequently Cry11Bb (Gutierrez et al, 2001), Cry5Ba (Xia et al, 2008), and Cry5Aa (Min et al, 2009) have been predicted by the homology modeling method. These reports have shown that these toxins have three structural domains.…”
Section: Introductionmentioning
confidence: 99%